2016
DOI: 10.1016/j.jacep.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Atrial Substrate Modification Guided by Electrogram Similarity and Phase Mapping Techniques to Eliminate Rotors and Focal Sources Versus Conventional Defragmentation in Persistent Atrial Fibrillation

Abstract: Our study showed that for persistent AF ablation, a specified substrate modification guided by nonlinear phase mapping could eliminate localized re-entry and non-pulmonary focal sources after pulmonary vein isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(105 citation statements)
references
References 24 publications
2
103
0
Order By: Relevance
“…Four studies reported a higher proportion of acute AF termination with driver‐guided ablation than in controls (pooled RR 2.08, 95% CI 1.43–3.05; P < 0.001), which increased to a RR 2.90 (95% CI 1.152–5.55, P = 0.001) when excluding patients undergoing driver‐guided ablation without concomitant PVI . Four studies suggested increased single‐procedure freedom from AF/AT at ≥1 year with driver‐guided ablation (RR 1.34, 95% CI 1.05–1.70; P = 0.02) though this was not significant when excluding cases of driver‐guided ablation without PVI (RR 1.41, 95% CI 0.96–2.08; P = 0.08) .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Four studies reported a higher proportion of acute AF termination with driver‐guided ablation than in controls (pooled RR 2.08, 95% CI 1.43–3.05; P < 0.001), which increased to a RR 2.90 (95% CI 1.152–5.55, P = 0.001) when excluding patients undergoing driver‐guided ablation without concomitant PVI . Four studies suggested increased single‐procedure freedom from AF/AT at ≥1 year with driver‐guided ablation (RR 1.34, 95% CI 1.05–1.70; P = 0.02) though this was not significant when excluding cases of driver‐guided ablation without PVI (RR 1.41, 95% CI 0.96–2.08; P = 0.08) .…”
Section: Resultsmentioning
confidence: 96%
“…Four studies suggested increased single‐procedure freedom from AF/AT at ≥1 year with driver‐guided ablation (RR 1.34, 95% CI 1.05–1.70; P = 0.02) though this was not significant when excluding cases of driver‐guided ablation without PVI (RR 1.41, 95% CI 0.96–2.08; P = 0.08) . Five studies suggested greater freedom from AF at ≥1 year (RR 1.29, 95% CI 0.99–1.69; P = 0.06) . This RR increased to 1.39 (95% CI 1.01–1.90; P = 0.04) when restricted to freedom from AF/AT after a single procedure and to 1.52 (95% CI 1.07–2.17; P = 0.02) when excluding patients who underwent driver‐guided ablation without PVI (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous work is unclear on whether CFAE are strongly 5 or less strongly 28 associated with drivers. Recent work by Chen et al suggest that specific electrogram patterns of dominant frequency and kurtosis 29 , or electrogram dispersion 30 may mark AF driver sites.…”
Section: Discussionmentioning
confidence: 99%